Nomenclatural novelties in Brazilian Verbenaceae - Cardoso, Pedro Henrique; Santana, Itajilanda Do Nascimento; Thode, Verônica A.; Silva, Tânia Regina Dos Santos; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2020)
Lippia subracemosa var. harleyi Moldenke and Verbena subpetiolata N.O’Leary, previously considered synonyms of Lippia lasiocalycina Chamisso and Glandularia jordanensis (Moldenke) N.O’Leary & P.Peralta, respectively, are being here recognized as distinct species in the genera Lippia and Glandularia. The nomenclatural changes needed are herein proposed: Lippia deltata I.N.Santana & T.R.S.Silva stat. & nom. nov. and Glandularia subpetiolata (N.O’Leary) P.H.Cardoso & V.Thode comb. nov. Comments on the distribution and morphological characters to differentiate these species from their most similar congeneric taxa are provided.